Effect of liquidity, leverage, and activity on profitability - Irawati Irawati; Dinda Cantika (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2022)
This research was carried out at the Karya Bersama Village Unit Cooperative in Kerubung Jaya Village for approximately six months. The purpose of this study is to analyze the effect of liquidity, leverage and activity on profitability. This research was conducted using a quantitative method where the researcher had obtained financial reports from the research site. Then the author conducted a feasibility test of the model and tested the hypothesis using the help of the twenty-first version of SPSS. The results of this study aim to obtain explanatory findings that are tested on (1) liquidity, leverage, and activity are not significant to profitability simultaneously in KUD. Joint Work in Kerubung Jaya. (2) Liquidity is partially insignificant to the profitability of KUD. Karya Bersama in Kerubung Jaya., (3) Leverage is partially insignificant to the profitability of KUD. Karya Bersama in Kerubung Jaya, (4) Activities are partially insignificant to the profitability of the KUD. Joint Work in Kerubung Jaya.